Congenital maxillomandibular fusion: Case series and review of the literature congenital syngnathia treatment approach - Othman Altuwairgi; Abdulsalam Aljabab; Ali Makrami; Ahmed Alomar; Yasir Alturkistany; Abu Bakarsharwani; Bushra Alhazmi; laila layqah; Ghufran Alayfan; Waleed Baharoon (Elsevier, 2022)
Congenital fusion of maxilla and mandible is a rare anomaly of uncertain etiology. It is broadly divided into two categories i.e. synechiae (soft tissue fusion) and synganthia (bony fusion). It has been proposed that defective stapedial artery during gestation or loss of neural crest cells may be major contributing factors, yet exact pathogenesis is still unknown. Surgery is the preferred mode of treatment but associated with high recurrence rates. Few cases involving the fusion of the mandible to the zygomatic complex have been reported. Herein, we present a series of 3patients with complete maxillomandibular syngnathia and hypoplastic mandible managed surgically at two local hospitals in Saudi Arabia.